Application of a household-based molecular xenomonitoring strategy to evaluate the lymphatic filariasis elimination program in Tamil Nadu, India. - Swaminathan Subramanian; Purushothaman Jambulingam; Brian K Chu; Candasamy Sadanandane; Venkatesan Vasuki; Adinarayanan Srividya; Mohamed S Mohideen AbdulKader; Kaliannagounder Krishnamoorthy; Harikishan K Raju; Sandra J Laney; Steven A Williams; Ralph H Henderson (Public Library of Science (PLoS), 2017)
BACKGROUND:The monitoring and evaluation of lymphatic filariasis (LF) has largely relied on the detection of antigenemia and antibodies in human populations. Molecular xenomonitoring (MX), the detection of parasite DNA/RNA in mosquitoes, may be an effective complementary method, particularly for detecting signals in low-level prevalence areas where Culex is the primary mosquito vector. This paper investigated the application of a household-based sampling method for MX in Tamil Nadu, India. METHODS:MX surveys were conducted in 2010 in two evaluation units (EUs): 1) a hotspot area, defined as sites with community microfilaria prevalence ≥1%, and 2) a larger area that also encompassed the hotspots. Households were systematically selected using a sampling interval proportional to the number of households in the EU. Mosquito pools were collected and analyzed by real-time polymerase chain reaction (qPCR). Two independent samples were taken in each EU to assess reproducibility of results. Follow-up surveys were conducted in 2012. RESULTS:In 2010, the proportion of positive pools in the hotspot EU was 49.3% compared to 23.4% in the overall EU. In 2012, pool positivity was significantly reduced to 24.3% and 6.5%, respectively (p<0.0001). Pool positivity based on independent samples taken from each EU in 2010 and 2012 were not significantly different except for the hotspot EU in 2012 (p = 0.009). The estimated prevalence of infection in mosquitoes, measured by PoolScreen, declined from 2.2-2.7% in 2010 to 0.6-1.2% in 2012 in the hotspot area and from 0.9-1.1% to 0.2-0.3% in the larger area. CONCLUSIONS:The household-based sampling strategy for MX led to mostly reproducible results and supported the observed LF infection trends found in humans. MX has the potential to be a cost-effective, non-invasive monitoring and evaluation tool with sensitive detection of infection signals in low prevalence settings. Further investigation and application of this sampling strategy for MX are recommended to support its adoption as a standardized method for global LF elimination programs.